Microsimulation models on child and adolescent health: a scoping review protocol - Filipa Sampaio; Claire de Oliveira (BMJ Open)
Introduction Microsimulation models are computer-based models, which can be employed to simulate the behaviour of microagents, such as children and adolescents, to understand the potential behavioural and economic effects of health interventions or policies. As a result, these models can be useful tools to help guide decision-making. A comprehensive review of the literature on child and adolescent microsimulation models has yet to be undertaken. Moreover, an evaluation of the quality of the existing models can be useful to understand their strengths and limitations and thus inform the development of future models. The aim of this scoping review will be to retrieve, synthesise and critically appraise the literature on existing microsimulation models focused on child and adolescent health.Methods and analysis We will conduct a scoping review using established methods. We will search PubMed (until 23 September 2024), Embase (until 18 September 2024), CINAHL (until 9 September 2024), PsyclNFO (11 September 2024), EconLit (until 9 September 2024) and Scopus (until 10 September 2024), with an update closer to the time of manuscript submission. We will also undertake snowballing, Google searches and searches on specific journal (eg, International Journal of Microsimulation) and websites (eg, https://www.microsimulation.ac.uk/) to complement database searches. We will extract relevant data on all studies retrieved and use the Quality Assessment Reporting for Microsimulation Models checklist to assess the reporting quality of each model. We will use a narrative synthesis with summary tables to describe our findings. Findings will be synthesised by type of health condition, if/where possible.Ethics and dissemination Given that primary data will not be collected in this study, research ethics approval is not required. We will present our findings at relevant conferences and publish our results in an appropriate peer-reviewed academic journal. In addition, we will use this information to guide the development of a microsimulation model on child and adolescent health for use in the Swedish context.Registration details https://osf.io/a8txn/